Glutathione Transferase Omega-1 Regulates NLRP3 Inflammasome Activation through NEK7 Deglutathionylation - Hooftman, Alexander; O'Neill, Luke (My University, 2019)
The NLRP3 inflammasome is a cytosolic complex sensing phagocytosed material and various damage-associated molecular patterns, triggering production of the pro-inflammatory cytokines interleukin-1 beta (IL)-1β and IL-18 and promoting pyroptosis. Here, we characterize glutathione transferase omega 1-1 (GSTO1-1), a constitutive deglutathionylating enzyme, as a regulator of the NLRP3 inflammasome. Using a small molecule inhibitor of GSTO1-1 termed C1-27, endogenous GSTO1-1 knockdown, and GSTO1-1-/- mice, we report that GSTO1-1 is involved in NLRP3 inflammasome activation. Mechanistically, GSTO1-1 deglutathionylates cysteine 253 in NIMA related kinase 7 (NEK7) to promote NLRP3 activation. We therefore identify GSTO1-1 as an NLRP3 inflammasome regulator, which has potential as a drug target to limit NLRP3-mediated inflammation.
PUBLISHED
Keywords: glutathione transferase omega 1-1 (GSTO1-1); NLRP3 activation; pro-inflammatory cytokines interleukin-1 beta (IL)-1β; GSTO1-1; IL-1β; NEK7; NLRP3 inflammasome; Deglutathionylation; Glutathione; Pyroptosis